Production and partial characterization of monoclonal antibodies to Bothrops asper (terciopelo) myotoxin - Lomonte, Bruno (1988)
Seven murine monoclonal antibodies against Bothrops aspen myotoxin were produced and partially characterized. They revealed the presence of at least four cross-reacting basic components in crude venom, with a common subunit mol. wt of 16,000 by sodium dodecylsulfate-polyacrylamide gel electrophoresis, but slight differences in charge. These myotoxin-related components might be isoforms of the toxin . By Western blotting and enzyme-immunoassay binding techniques, differences in the reactivities with basic venom fractions were observed among monoclonal antibodies, suggesting differences in epitope specifidties . Three antibodies cross-reacted with B. nummifer crude venom. Two monoclonal antibodies were utilized to develop a two-site enzyme-immunoassay for myotoxin detection at the nanogram level . Three of the antibodies (one IgM and two IgG,) showed ability to neutralize myotoxiclty of purified myotoxin in preincubation-type experiments.